2019
DOI: 10.2147/ijn.s176013
|View full text |Cite
|
Sign up to set email alerts
|

<p>Amelioration of diabetic nephropathy using pomegranate peel extract-stabilized gold nanoparticles: assessment of NF-&kappa;B and Nrf2 signaling system</p>

Abstract: Background: Diabetic nephropathy (DN), an end-stage renal disorder, has posed a menace to humankind globally, because of its complex nature and poorly understandable intricate mechanism. In recent times, functional foods as potential health benefits have been gaining attention of consumers and researchers alike. Rich in antioxidants, the peel and seed of pomegranate have previously demonstrated protection against oxidative-stress-related diseases, including cardiovascular disorders, diabetes, and cancer. Purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 49 publications
8
53
0
1
Order By: Relevance
“…The histopathological findings were in consistence with the study of [55][56] who found significantly reduced vacuolar degeneration of tubules of the kidney and reduction of the thickened basement membrane in diabetic rats treated with PGPE.…”
Section: Discussionsupporting
confidence: 82%
“…The histopathological findings were in consistence with the study of [55][56] who found significantly reduced vacuolar degeneration of tubules of the kidney and reduction of the thickened basement membrane in diabetic rats treated with PGPE.…”
Section: Discussionsupporting
confidence: 82%
“…Hyperglycemia and oxidative stress are important factors in the development of diabetic microvascular complications including DN [15,16]. Recent studies have demonstrated that pomegranate peel extract-stabilized 20-nm AuNPs and 13nm naked AuNPs reduced STZ-induced renal fibrosis, inflammation, and oxidative stress [17,18]. However, the maximized kidney targeting at the cellular (mesangium), tissue, and organ levels will be achieved via the usage of 50-nm AuNPs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of ROS induced the phosphorylation of three MAPKs, including JNK, ERK, and p38 [48]. Manna et al [49] reported that pomegranate peel extract-stabilized GNPs reduced the pro-inflammatory burden by modulating the MAPK and NF-jB pathways. In the current study, the phosphorylated form of ERK and p38 was decreased by GNP-CK-CopA3 in LPS-stimulated RAW264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%